O ensino do desenho na escola normal de Belo Horizonte (1906-1946) - Ismael Krishna de Andrade Neiva (2016)
This thesis aims to understand how was the process of schooling drawing in the Normal School of Belo Horizonte. By using a variety of sources such as notebooks and class daily, teaching materials, assessment, curriculum and daily records of the Normal School, the work inquires about the school routine, on the methodology and the didactic design of teaching and the spaces intended for this discipline. In this sense, related to those issues to the political, artistic and cultural context present in Brazil and Belo Horizonte between 1906 and 1946, operating period of the Normal School. The research aims as well to see how the design was educated and worked in the Normal school, understand and understand the role of this discipline in school life, in civic and patriotic festivities, understanding how his actors, teachers and students, dialogued with the community school and non-school. Another important issue and it becomes one of the research objectives is to understand the role of intellectuals and artists, acting as teachers at the Normal School, harnessed the contents worked to their tastes and artistic principles. Inserted in the field of history of school subjects, the thesis proposes to extend the research on school education in Minas Gerais.